PERAN E-WOM MEMEDIASI VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN JAFRA COSMETICS INTERNASIONAL DI KOTA KENDARI - Indri Hapsari; Hairudin Bugis; Irelda Sari Syaranamual; Usman; Siti Nurkhalisa (Halu Oleo University, 2024)
Decisions regarding purchasing JAFRA Cosmetics International products are often influenced by other individuals, friends and communities. Along with technological advances and the development of social media with viral marketing E-WOM has an impact in terms of positive and negative statements of consumer behavior. The purpose of the study was to determine the influence of viral marketing on purchasing decisions of Jafra products mediated by E-WOM. This study used an explanatory type of research using a quantitative approach. The population of this study is Jafra consumers in Kendari City. The sampling technique uses Purposive sampling of 50 respondents from consumers of Jafra products and data analysis techniques using Smart-PLS. The results showed that Viral Marketing does not directly affect Purchasing Decisions, but the existence of E-WOM is able to mediate Viral Marketing to affect JAFRA Cosmetics International Purchasing Decisions in Kendari City. The mediation variable model found in this study is that E-WOM has a role as a perfect mediation (Complete mediation). In this case, E-WOM has a greater impact on more effective marketing communications.